PROTECTION OF THE BRAND RIGHTS OF THE FRANCHISOR IN THE FRANCHISE AGREEMENT - Senjaya, Pierre; Harjono, Dhaniswara; Betlehn, Andrew (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
The main problem in this research focuses on how franchise businesses relate to problems that arise and often occur in franchise businesses. On this occasion the researcher explained the problems that emerged clearly. Based on normative juridical qualitative research, it was found that there are many problems in franchise businesses that always arise and the increasing number of franchise businesses appearing in society shows the importance of conducting studies related to legal protection for these businesses in Indonesia. Several ways to minimize the risk of legal problems in a franchise business include making a clear and complete franchise agreement, carrying out due diligence before entering into a franchise collaboration, understanding the laws and regulations related to franchise businesses, building good communication between franchisor and franchisee and providing training. and education for franchisees. By understanding the legal problems that often occur in franchise businesses and the steps to prevent them, franchisors and franchisees can minimize risks and build a successful franchise business